2009
DOI: 10.1016/j.geomorph.2007.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic acceleration of sediment accretion in lowland floodplain wetlands, Murray–Darling Basin, Australia

Abstract: Over the last decade there has been a deliberate focus on the application of paleolimnological research to address issues of sediment flux and water quality change in the wetlands of the Murray-Darling Basin of Australia. This paper reports on the research outcomes on cores collected from sixteen wetlands along the Murrumbidgee-Murray River continuum. In all sixteen wetlands radiometric techniques and exotic pollen biomarkers were used to establish sedimentation rates from the collected cores. Fossil diatom as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 20 publications
1
48
0
12
Order By: Relevance
“…A rapid increase in sedimentation rates associated with European settlement is seen across Australia. Studies of wetlands and lakes across southern Australia have revealed increases from 2-to 80-fold between pre-settlement and modern day (Gell et al, 2009;Hollins et al, 2011;Sloss et al, 2011). This phenomenon is important for separating human and climatic influences on sediment cores.…”
Section: Lithicsmentioning
confidence: 96%
See 1 more Smart Citation
“…A rapid increase in sedimentation rates associated with European settlement is seen across Australia. Studies of wetlands and lakes across southern Australia have revealed increases from 2-to 80-fold between pre-settlement and modern day (Gell et al, 2009;Hollins et al, 2011;Sloss et al, 2011). This phenomenon is important for separating human and climatic influences on sediment cores.…”
Section: Lithicsmentioning
confidence: 96%
“…This also allows for non-linear accumulation rates (Goring et al, 2012), which is an important consideration in the Australasian context. For example, a rapid increase in sedimentation rate is known to correspond to European settlement in Australia (Gell et al, 2009) and changes in land cultivation practices in the Malay Archipelago (Gharibreza et al, 2013;Rodysill et al, 2012).…”
Section: Age Model Recalibrationmentioning
confidence: 99%
“…Deforestation of the catchment became widespread during the expansion of agriculture. As a result, the majority of wetlands have been subjected to significant bank erosion and sedimentation (Gell et al, 2009). In China, similar contemporary pressure has been placed on the Yangtze River system, where similar largescale modifications of rivers and wetlands occurred during the 1950s-1970s.…”
Section: Introductionmentioning
confidence: 99%
“…A mezőgazdasági tevékenység többféle módon okozhat a folyó alsóbb szakaszain intenzív ártérfeltöltődést: például a földterületek feltörése kapcsán, amikor a vízgyűjtő egyes részeit mezőgazdasági művelés alá vonják (Florsheim és Mount 2003) -különösen látványos ez olyan ausztráliai vagy észak-amerikai vízgyűjtőkön, ahol az európaiak modernkori megtelepedése előtt az őshonos lakók alig alakították át környezetüket (Rustomji és Pietsch 2007, Gell et al 2009, Hughes et al 2010. Például Brierley és Murn (1997) kutatása szerint Ausztráliában a Cobargo vízgyűjtő az európaiak betelepülése előtt természetesen fejlődött: a felső vízgyűjtőn a vízfolyás nem volt bevágódva, az alsóbb szakaszokon mocsaras területek voltak.…”
Section: A) a Területhasználat Változás Hatása Az áRterek Feltöltődéséreunclassified